Representation of Islamic Education Values in the Wayang Kekayon Khalifah Lakon Pandanarang Malik Grembyang - Hidayat, Kun; Rahman, Arif; Islahuddin, Islahuddin; Ichsan, Yazida (Al-Misbah (Jurnal Islamic Studies), 2023)
Islamic education as part of society's value system cannot be separated from cultural elements. Therefore, the relationship between Islamic education and culture can be an appropriate collaboration in overcoming shifts in values among society. The aim of this research is to represent the values of Islamic education in the Wayang Kekayon Khalifah play Pandanarang Malik Grembyang, which also looks at the implementation of its value content on the social system. This research uses the hermeneutic phenomenology method to study the play text textually and contextually. The results of the research show that the play contains the essence of the dangers of life that deifies the world or the despicable behavior of one's culture. So, the Pandanarang play in the Wayang Kekayon Khalifah art becomes relevant when it is presented to a community that is starting to experience a shift in values. The implications of this research reflect a cultural approach as optimizing Islamic education in society.